2019
DOI: 10.1002/er.5048
|View full text |Cite
|
Sign up to set email alerts
|

Rose pattern for heliostat field optimization with a dynamic speciation‐based mutation differential evolution

Abstract: Summary Concentrated solar power technology is one of the most promising technologies in energy field. Arguably, the heliostat field layout is a crucial component in solar power tower system. Numerous studies have been developed for heliostat field optimization. However, most of the existing layouts which utilize radial staggered patterns are based on only two or four variables, leading to relatively rigid modes due to strong configuration constraints. In this article, we propose a new method called rose layou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…To calculate the collector truncation efficiency, we adopted the method proposed by Collado and Guallar, based on the HFLCAL model [3]:…”
Section: Collector Truncation Efficiencymentioning
confidence: 99%
“…To calculate the collector truncation efficiency, we adopted the method proposed by Collado and Guallar, based on the HFLCAL model [3]:…”
Section: Collector Truncation Efficiencymentioning
confidence: 99%
“…The proposed algorithm, the Artificial Bee Colony Algorithm (IABCA), finds the best position for each heliostat on the field in which the maximum efficiency for both the heliostat and field is reached within a limited area. L Deng et al [23] proposed a new pattern for the heliostat field layout: a rose pattern based on the classic radial staggered configuration. The pattern divides the radial staggered configuration into six sectors, and some of those sectors are then optimized separately using advanced differential equation algorithm, thus increasing the optimization variables.…”
Section: Introductionmentioning
confidence: 99%
“…The computed daily and monthly averaged annual optical efficiency were found equal to 0.5023 and 0.5025, respectively. Very recently, Deng et al 26 proposed a new method named rose layout based on the split of the regular radial staggered pattern into six sectors, then the optimization process is carried out separately for each divided sector. Authors reported that the advantage of this method is that it is more efficient and flexible as the radial increments between consecutive rows are relevant its corresponding sector and are not constrained to zones or rows.…”
Section: Introductionmentioning
confidence: 99%